2009
DOI: 10.1093/cvr/cvp139
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resveratrol-induced platelet apoptosis

Abstract: This study demonstrates for the first time that resveratrol simultaneously inhibits platelet aggregation and stimulates platelet apoptosis. Stimulation of platelet apoptosis by resveratrol may represent the increased therapeutic potential for patients suffering from thrombotic conditions or thrombocytosis to promote platelet destruction and thus prevent pathological clotting. Furthermore, this study also provides a novel conception that rigorous surveillance of platelet numbers may be important during resverat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 34 publications
1
92
0
Order By: Relevance
“…Previously, studies have explored the pro-apoptotic effects of therapeutic compounds such as resveratrol and thymoquinone [7,34]. The current piece of work stresses upon the pro-apoptotic effects of yet another therapeutic compound sesamol, at concentrations higher than 0.25 mM on human platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, studies have explored the pro-apoptotic effects of therapeutic compounds such as resveratrol and thymoquinone [7,34]. The current piece of work stresses upon the pro-apoptotic effects of yet another therapeutic compound sesamol, at concentrations higher than 0.25 mM on human platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Res is mainly used as a nutritional supplement in terms of its effects on cardiovascular protective (26), antiplatelet (27), antioxidant (28), antiinflammatory (29) and blood glucoselowering (30). Emerging evidence indicated that Res has been shown to suppress proliferation of various tumor cells, such as colon cancer (31), but the mechanism of anticancer activity for Res has not been completely elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets, the enucleate blood cells derived from megakaryocytes, are discoid in shape, with size ranging between 2-4 m. In response to vascular injury, platelets tether, adhere, aggregate, and finally form platelet plugs in injured vessel walls to arrest bleeding from blood vessels (11). HDAC inhibition has been reported previously to affect platelet function (12,13).…”
mentioning
confidence: 99%